Isotemporal Substitution of Sedentary Behavior by Different Physical Activity Intensities on Pain and Disability of Patients With Chronic Low Back Pain: A Cross-Sectional Study - Freire, Ana Paula Coelho Figueira; Oliveira, Crystian Bitencourt Soares de; Christofaro, Diego Giulliano Destro [UNESP]; Shumate, Sean; Marques, Larissa Bragança Falcão; Pinto, Rafael Zambelli (Elsevier, 2022)
Objective: To investigate the association of isotemporal substitution modeling (ISM) of time spent in sedentary activities with physical activity in different intensities on pain and disability of patients with chronic low back pain (LBP). Design: Observational and cross-sectional study. Device-measured physical activity levels were assessed using an actigraph. Pain intensity was measured using the 11-point numeric rating scale, and disability was measured using the Roland Morris Disability Questionnaire. The ISM was used to estimate the theoretical substitution association of reallocating time from 1 exposure variable to an equal amount of time in another exposure variable while holding total activity time constant. Settings: Outpatient physical therapy clinic. Participants: This study included data from 358 patients (N=358) with chronic LBP aged between 18 and 60 years. Main Outcome Measures: Pain and disability. Results: Our results suggest that replacing 60 minutes of sedentary behavior with 60 minutes of vigorous activity in a week is significantly associated with a decrease in pain (β=−1.67; 95% confidence interval [CI], −3.18 to −0.15). Additionally, replacing 60 minutes of light physical activity (β=−1.67; 95% CI, −3.18 to −0.16) or moderate activity (β=−1.67; 95% CI, −3.21 to −0.13) with the same amount of time of vigorous activity per week may also favorable reductions in pain. For the analysis of disability, no significant associations (P>.05) for disability in any of the isotemporal models were found. Conclusions: Our results showed that replacing 60 minutes of sedentary behavior with equal amounts of vigorous activity per week was associated with reductions in pain intensity. Similarly, replacing a light or moderate activities with vigorous activity was also associated with reductions in pain intensity. Finally, no significant associations were observed between time spent in sedentary activities with physical activity in different intensities for disability.
Keywords: Exercise; Low back pain; Rehabilitation; Sedentary behavior